Glycolipids: Linchpins in the Organization and Function of Membrane Microdomains - Hanafusa, Kei; Hotta, Tomomi; Iwabuchi, Kazuhisa (Frontiers in Cell and Developmental Biology, 2020)
Membrane microdomains, also called lipid rafts, are membrane areas in which glycolipids, sphingolipids and cholesterol are enriched. Although membrane microdomains are thought to play key roles in many cellular functions, their structures, properties, and biological functions remain obscure. Cellular membranes contain several types of glycoproteins, glycolipids and other lipids, including cholesterol, glycerophospholipids and sphingomyelin. Depending on their physicochemical properties, especially the characteristics of their glycolipids, these membranes form various microdomains, providing structural or functional contextures on cell membranes thought to be essential for biological activities. For example, the plasma membranes of human neutrophils are enriched in lactosylceramide (LacCer) and phosphatidylglucoside (PtdGlc). Each of these glycolipids forms different membrane microdomains with different surrounding molecules, and are involved in different functions of neutrophils. Specifically, LacCer forms Lyn-coupled lipid microdomains, which mediate neutrophil chemotaxis, phagocytosis and superoxide generation, whereas PtdGlc-enriched microdomains mediate neutrophil differentiation and spontaneous apoptosis. However, the mechanisms by which these glycolipids form different nano/meso microdomains and mediate their specialized functions remain incompletely understood. This review describes current understanding of the roles of glycolipids and sphingolipids in their enriched contextures on cellular membranes, including their mechanisms of facilitation and regulation of intracellular signaling. This review also introduces new concepts about the roles of glycolipid- and sphingolipid-dependent contextures in immunological functions.